Inovasi Kemasan Kertas Benih Ramah Lingkungan Berbahan Dasar Kulit Jagung dan Ampas Tebu - Ihlana Nairfana; Chairul Anam Afgani; Imam Munandar (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Experimental research was carried out to obtain formulations of corn husk and sugarcane bagasse to produce good quality seed paper packaging. The differences in the raw material formulations used were (70% corn husk : 30% bagasse), P2 (50% corn husk : 50% bagasse) and P3 (30% corn husk : 70% bagasse). The research data were analyzed using ANOVA and for each treatment that was significantly different it was continued with the Duncan Multiple Range Test (DMRT) at the 5% confidence level. The results showed that corn husks and bagasse could be used as raw materials for paper, with a characteristic of yellow to brown in color, and were able to be formed into paper pouch packaging. Based on statistical analysis using ANOVA at α level of 5%, P3 treatment (25% corn husk : 75% bagasse) is the best treatment which produces paper packaging with the strongest tensile strength (12.1 N), the best elasticity (14.4%), as much as 65% can decompose in the soil after being planted for 4 weeks, and the seeds managed to germinate on the 9th day after the paper was planted.